(untitled) (Szociológiai Szemle, 2024)
One o f the most suitable methods of research among the Romany people is interview by questionnaire. However, to that the definition o f multitude is needed which - as an ethnic group is involved - should also be based on constructs. We have analysed the situation of the Romany population on the basis o f the results of the survey conducted by the Szonda lpsos on a very large national representative sample in 1997. Approximately 2-2.5 thousand Romany respondents were included in the sample which allowed for the study of the population divided into several groups. As a result we have set up four groups out of the entire sample (of 26,800 people) on the basis o f three criteria (the questioner’s opinion, the respondent’s opinion about him or herself, the respondent’s answer concerning the nationality of parents): 1. “non-Romany” - those who were not registered as Gypsies by the questioners, or neither o f the parents was Gypsy, or the respondent did not regard him- or herself Romany; 2. “uncertain” - those about whom the questioner could not decide whether the respondent was Romany, and the questioned did not regard him- or herself Romany; 3. “stigmatised” - those who were classified as Romany by the questioner, while they did not regard themselves, nor their parents Romany; 4. “admissive” — those about whom the questioner as well as the respondent stated that the person concerned was of Romany ethnicity. The living conditions (age, school education, economic activity, occupation, income) of people belonging to the different groups show significant differences. At the same time the sharpest difference was not between the ’non-Romany’ and the other categories, but between the situation of the ’admissive’ ones and the rest. We have investigated the influence of marriage among those who mentioned Romany ancestors. According to the experiences of the survey the school education of those born in a mixed (Romany and non-Romany) marriage was much higher than in the case of those born from a homogenous Romany marriage. In the majority of mixed marriages Romany men of high status would marry non-Romany women, and children born in such a family would have school education going beyond that of the father. In a smaller part of marriages low status non-Romany men would marry Romany women, however, in such families the school education of the children often does not even reach the level of their fathers.